(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Data on the specific composition, dynamics of populations, and similarities among phytoseiid species associated with various cultivated and spontaneous plants present in a complex agroecosystem, are here reported. 11 species, belonging to 7 genera, have been collected. Euseius stipulatus (Athias-Henriot) was the most frequently found species on all the surveyed plants, followed by Euseius finlandicus (Oudemans) (91%). Typhlodromus exhilaratus Ragusa and Amblyseius andersoni (Chant) were found on 73% of plants, while the remaining species were sporadically collected. E. stipulatus was the dominant species on vines, on spontaneous herbaceous plants and asparagus, maize and turnip tops, while E. finlan-dicus was the dominant species on nuts, tomatoes and potatoes. High values of similarity were ascertained between the two cultivars of vines, spontaneous herbaceous plants present between rows and white willows (0.80-0.89) as well as between nuts and asparagus (0.71). The data obtained and analysed show an exchange of phytoseiid species among the different plant species present in the agroecosystem even if the permanence of the various species on various plants is most probably linked to the preference of each species towards the habitats offered by the various plants.